When the opportunity knocks: Large structural shocks and gender wage gaps - Joanna Tyrowicz; Lucas Van der Velde (Leibniz-Institut für Ost- und Südosteuropaforschung (IOS), 2018)
Undergoing a large structural shock, labor markets may become less inclusive. We test for this thesis analyzing the behavior of adjusted gender wage gaps in a wide selection of transition countries. We estimate comparable measures of adjusted gender wage gaps for a comprehensive selection of transition countries over a period spanning nearly three decades. We combine these estimates with measures of labor market reallocation in transition economies. We identify the episodes of particularly large labor market reallocations and observe the behavior of the gender wage gaps subsequent these episodes, and exploit the discontinuity between the cohorts participating in the labor market prior to the onset of transition and cohorts of subsequent entrants. Our analysis reveals a distinctive role played by separations from the state-owned manufacturing firms, leading to greater adjusted gender wage gaps. In the medium run the adverse effects of separation hikes from this sector are even more pronounced.
urn:nbn:de:101:1-2019040812023474369400
Keywords: C24; J22; J31; J71; 330; gender wage gap; transition; non-parametric estimates; worker flows